Karakterisasi Aliran HilirKipas Aksial sudu Datar Variasi Span Sudu dan Sudut Serang - Joko Waluyo; Sutrisno S (Forum Teknik, 2003)
Abstract The velocity field downnstream of an axial fan was measured using probe 55 P 51 of a Hot Wire Anemometer to investigate characteristic of the flow. Flat blades werevaried in length of blade's span and angle of attock. The length of blade's span was varied at 0.3, 0'5, 0.75 and l times of 450 mm, at various angles of attack at 5º, 10º and I5º, while it was operated at constant speed of 610 rpm. The measurement was conducted at vertical distances 210, 360, 510 and 660 mm from the fan. The investigation was focused on the mean velocity in axial and tangential directions at measurement position 210 mrn. Properties of theflow were computed based on integration of Reynolds momentum and continuity equations for determining flux of axial and angularmomentum. The performance of the axial fan was determined by comparing values of torque, thrust, volume rate and consumed power. The swirling number of the flow was also calculated as a consideration to determine performance of the axial fan. Results indicate that operating the axial fan in variation blade'sspan have significant effect to the value of axial and tangential mean velocities and the area off low, meanwhile variation in angle of attack just influence to the value of axial and tangential mean velocities. Increasing ofblade's span at constant angle of attack If increases volume rate, torque, and thrust of flow and consumed power oJ'the fan. Investigation of increasing angle of attack at span blade 450 mm also increases those values. Span blade 450 mm at angle of attack l5º have a highest performance and consumed power. It can be shown also that swirling increase with respect to increase of angle of attack. Keywords: velocityfield downstream axial flowfan, span's blade,angle of attack.